The castaway's war : one man's battle against Imperial Japan - Harding, Stephen, 1952- (Da Capo Press, a member of the Perseus Books Group, 2016)
"Presents the story of Lieutenant Hugh Barr Miller, who was marooned on a South Pacific island and waged a one-man war against Japanese forces. By the author of The New York Times best-seller The Last Battle,"--NoveList.